Pengaruh kompensasi terhadap kompetensi guru melalui motivasi sebagai variabel intervening di SD Negeri 228 Sarolangun - Rahim, Kasmir; Rosita, Sry; Sumarni, Sumarni (Jurnal Dinamika Manajemen, 2021)
This study aims to determine the effect of compensation on teacher competence through motivation as an intervening variable at SD N 228 Sarolangun. The sample in the study amounted to 15 people. The data collection method used a literature study and questionnaires, measured by the Likert scale. Analysis using descriptive and quantitative analysis using the analysis tool is SmartpPLS 3.0. Based on the results of research conducted on the Effect of Compensation on Competence through Motivation as an Intervening Variable at SD N 228 Sarolangun. Then the results obtained show that compensation has a positive and insignificant effect on teacher competence, compensation has a positive and significant effect on motivation, and work motivation has a positive and insignificant effect on competence. The results show that compensation through motivation as an intervening variable has a positive and insignificant effect on teacher competence in SD N 228 Sarolangun.